Homozygous Smpd1 deficiency aggravates brain ischemia/ reperfusion injury by mechanisms involving polymorphonuclear neutrophils, whereas heterozygous Smpd1 deficiency protects against mild focal cerebral ischemia - Hagemann, Nina (Basic Res Cardiol, 2020)
By cleaving sphingomyelin into ceramide, which is an essential component of plasma membrane microdomains, acid sphingomyelinase (Asm) pivotally controls cell signaling. To define how the activation of the Asm/ceramide pathway, which occurs within seconds to minutes upon stress stimuli, influences brain ischemia/reperfusion (I/R) injury, we exposed male and female wildtype mice carrying both alleles of Asm’s gene sphingomyelinase phosphodiesterase-1 (Smpd1(+/+)), heterozygously Asm-deficient mice (Smpd1(+/−)) and homozygously Asm-deficient mice (Smpd1(−/−)) of different age (8, 12 or 16 weeks) to 30, 60 or 90 min intraluminal middle cerebral artery occlusion (MCAO). For studying the contribution of brain-invading polymorphonuclear neutrophils (PMN) to I/R injury, PMNs were depleted by delivery of a PMN-specific Ly6G antibody. In male and female mice exposed to 30 min, but not 60 or 90 min MCAO, homozygous Smpd1(−/−) consistently increased I/R injury, blood–brain barrier permeability and brain leukocyte and PMN infiltration, whereas heterozygous Smpd1(+/−) reduced I/R injury. Increased abundance of the intercellular leukocyte adhesion molecule ICAM-1 was noted on cerebral microvessels of Smpd1(−/−) mice. PMN depletion by anti-Ly6G delivery prevented the exacerbation of I/R injury in Smpd1(−/−) compared with wildtype mice and reduced brain leukocyte infiltrates. Our results show that Asm tempers leukocyte entry into the reperfused ischemic brain, thereby attenuating I/R injury. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00395-020-00823-x) contains supplementary material, which is available to authorized users.